Spiritual well-being promotion for older adults: Implication for healthcare policy makers' decision making on cost savings - Nader Aghakhani; Claire Su-Yeon Park (Wolters Kluwer Medknow Publications, 2019)
A spiritual well-being-based nursing intervention may boost older adults' resilience-based recovery. Its potential contribution may have positive knock-on effects: controlling skyrocketing healthcare costs; reducing the productive population's social burden of supporting the older adults; and alleviating a generational conflict. However, healthcare policy-makers are still skeptical about investing in those healthcare resources which would develop and implement a spiritual well-being-based nursing intervention for older adults. It is time for nurse scientists, as front-line gatekeepers for patients' omnidirectional well-being, to escape from thinking within the box by actively addressing first the feasibility, then the direct and indirect effectiveness on actual patient outcomes, and finally the cost efficiency of a spiritual well-being-based nursing intervention for the added benefit of easing the decision-making of healthcare policy-makers.